Density and Attendance Frequency of Seagrass In Coastal Waters of Porto Village, Saparua Island, Central Maluku - A. Lewerissa, Yona (Fakultas Pertanian, Universitas Muhammadiyah Maluku Utara, 2023)
Seagrass acts as a food source in supporting the productivity of the living creatures that lives sorrounds, rearing areas, and sediment filtering systems. The Village of Porto is one of the coastal villages that has a fairly extensive seagrass ecosystem. Seagrass, locally known as